Fractional-Based Stochastic Gradient Algorithms for Time-Delayed ARX Models - Xu, Tianyang; Chen, Jing; Pu, Yan; Guo, Liuxiao (Circuits, systems, and signal processing, 2022)
In this study, two fractional-based stochastic gradient (FSG) algorithms for time-delayed auto-regressive exogenous (ARX) models are proposed. By combining momentum and adaptive methods, a momentum-based FSG and an adaptive-based FSG algorithms are developed. These two FSG algorithms have faster convergence rates when compared with the stochastic gradient algorithm. The mechanism of the convergence is proved in theory. Furthermore, two simulated examples are presented to illustrate the efficiency of the new proposed algorithms.